New (2+1) and (3+1)-dimensional Integrable Boussinesq Equations: Multiple Soliton Solutions - Wazwaz, Abdul-Majid (Journal of Applied Nonlinear Dynamics, 2026)
In this work, we investigate new (2+1) and (3+1)-dimensional Boussinesq equations. We show the complete integrability of these equations via using the Painlevé test. We derive multiple soliton solutions for each model by using the simplified Hirota’s method. Other exact solutions of physical structures are determined.